Traditional Phytotherapy for Diabetes Used by the People of Perambalur District, Tamilnadu, South India - V.Gomathi, R. Rajendran, D. Devendrakumar, M. Anbazhagan (Recent Research in Science and Technology, 2009)
Diabetes is caused due to deficiency in production of insulin by the pancreas, or by the ineffectiveness of the insulin produced. It is a global problem and the numbers of people affected are increasing day by day. Plants provide a potential source of antidiabetic drugs. In India, most of the people, especially in rural areas use traditional medicine of plants to treat many diseases including diabetes. The aim of the present study was to document medicinal plants, traditionally used to treat diabetes by the people of Perambalur district. Traditional health practitioners were interviewed with standardized questionnaires in order to obtain information on medicinal plants traditionally used for the management of diabetes. Thirty species of 29 genera and 22 families were encountered during this study.